Sialic acid as a biomarker of oral potentially malignant disorders and oral cancer - Sonika Achalli; Medhini Madi; Subhas G Babu; Shishir Ram Shetty; Suchetha Kumari; Supriya Bhat (Wolters Kluwer Medknow Publications, 2017)
Background: Carcinogenesis is a multistep process where a healthy cell has initially a precancerous stage and finally an early cancerous stage. The process of carcinogenesis can be divided into three stages of initiation, promotion, and progression. In this process, there is increased turnover, secretion, and/or shedding from malignant cells. Glycoproteins like sialic acid are expressed on the cell surface. In oral potentially malignant disorders (OPMDs) and oral cancer (OC), the sialic acid level is seen to increase due to high cell turnover and shedding of malignant cells which, in turn, results in the release of glycoproteins like sialic acid into circulation. Glycoproteins also form an important constituent of salivary mucins and hence due to the same mechanism, an increase in sialic acid level is also seen in saliva. Objective: The aim is to estimate serum and salivary sialic acid levels in healthy controls, patients with OPMDs and patients with OC. Materials and Methods: In this observational cross-sectional study, serum and salivary sialic acid levels were estimated in thirty healthy controls, thirty patients with OPMDs and thirty patients with OC. Results: Serum and salivary sialic acid levels obtained were subjected to statistical analysis. Post hoc Tukey test was used to compare the serum and salivary sialic acid levels of the two study groups to the control group. ANOVA test was used for the comparison of sialic acid levels between the groups. Pearson's correlation coefficient was used to assess correlation (P < 0.05 was considered statistically significant). The mean serum and salivary sialic acid levels were increased significantly in subjects with OPMDs and OC when compared to healthy controls. Conclusion: This study highlights the high expression of sialic acid on outer cell membranes, due to the significant increase in subjects with OPMDs and OC when compared to healthy controls. A significant increase in sialic acid level is also seen in saliva. Hence, it can be stated that saliva can be used as a reliable, noninvasive tool in diagnosis and management of OPMDs and OC.